2019
DOI: 10.1007/s11547-019-01052-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem computed tomography (PMCT) radiological findings and assessment in advanced decomposed bodies

Abstract: The aim of the study is to report radiological findings and features in advanced decomposed bodies obtained by post-mortem computed tomography (PMCT) with autopsy correlation. Materials and methods This retrospective descriptive multicentric study included 41 forensic cases examined between May 2013 and November 2016. All the bodies were PMCT-scanned prior to autopsy, and internal putrefactive state was determined using the radiological alteration index (RAI) by a radiologist with expertise in forensic radiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…PMCT is sensitive in detecting these changes, but careful interpretation of the imaging is required to avoid diagnostic pitfalls. 18 We find that PMCT has utility as an adjunct in the examination of decomposing bodies and that there are instances where it allows an invasive examination to be dispensed with. Cartocci et al have suggested that the benefit of PMCT in these cases lies in the detection of putrefactive gas, 18 but we disagree and consider this to be of no benefit.…”
Section: Decomposing and Embalmed Bodiesmentioning
confidence: 81%
See 2 more Smart Citations
“…PMCT is sensitive in detecting these changes, but careful interpretation of the imaging is required to avoid diagnostic pitfalls. 18 We find that PMCT has utility as an adjunct in the examination of decomposing bodies and that there are instances where it allows an invasive examination to be dispensed with. Cartocci et al have suggested that the benefit of PMCT in these cases lies in the detection of putrefactive gas, 18 but we disagree and consider this to be of no benefit.…”
Section: Decomposing and Embalmed Bodiesmentioning
confidence: 81%
“…18 We find that PMCT has utility as an adjunct in the examination of decomposing bodies and that there are instances where it allows an invasive examination to be dispensed with. Cartocci et al have suggested that the benefit of PMCT in these cases lies in the detection of putrefactive gas, 18 but we disagree and consider this to be of no benefit. Rather, we consider that PMCT is helpful in identifying foreign bodies 19 such as pacemakers or other implanted devices, suggesting cardiac disease, and also plays a role in body identification.…”
Section: Decomposing and Embalmed Bodiesmentioning
confidence: 81%
See 1 more Smart Citation
“…Students have enough space to explore and study anatomical structures during cadaver dissection. Autolytic gas formation can cause limited data quality of some PMCT scans (Sapienza et al, 2017; Cartocci et al, 2019). This together may explain the comparably high scores of CCD for abdominal anatomy.…”
Section: Discussionmentioning
confidence: 99%
“… 103 The RAI is a semiquantitative estimation of the extent of postmortem gas formation in seven anatomical locations as graded from 1 to 3 on PMCT, and has been demonstrated to correlate well with the grade of external putrefaction. 104 …”
Section: Methods and Analysismentioning
confidence: 99%